Supervision of Road Maintenance Implementation at the Self-Managed Technical Implementation Unit (UPTD) Road and Bridge Maintenance of Public Works and Spatial Planning Agency of Banjarmasin City Government - Fadhillah, Muhammad Lufi; Irawanto; Jamili, Muhammad (Formosa Journal of Social Sciences (FJSS), 2024)
This study evaluates the supervision of road maintenance implementation by the government, with the aim of identifying inhibiting factors and proposing efforts to overcome them. The research approach was qualitative, with the Head of the Road Division as the key informant and Section Heads and staff as additional informants. Data collection methods included observation, interviews and documentation, and data were analyzed using an interactive analysis model. The identified inhibiting factors include the lack of apparatus quality, inadequate work facilities and infrastructure, insufficient road supervision funds, not optimal utilization of apparatus resources, and inappropriate apparatus placement. Efforts made to overcome these factors include improving the quality of human resources, improving facilities and infrastructure, allocating larger budget funds, implementing supervision programs based on needs analysis, making officer development plans, and evaluating project supervisory employees. By overcoming these inhibiting factors and implementing these efforts, it is expected to increase the effectiveness of road maintenance supervision and provide better road conditions for the community